Modifikasi Keramik Kerajinan Rakyat dengan Penambahan CaSO4, Pasir Besi, Abu Sekam Padi, dan Batu Kapur - Zilfa, Z.; Vivi Sisca (Departemen Kimia Universitas Andalas, 2023)
One of the ceramic home industries is ceramic making in Galogadang Batusangkar. This home industry uses the basic ingredients of clay mixed with water and then molded and burned, so the resulting ceramic products are less than perfect, hard, and brittle. According to the matter above, we wish to try to look for methods and modify the ceramics home industry by adding some clay that turns yellow and white, sulfate calcium (CaSO4), limestone, iron sand, and chaff ash. The process of ceramic consists of three phases that are pressing powder, drying, and burning. The analysis carried out is the compressive strength test, and SEM (Scanning Electron Microscopy) aims to observe the uniformity of the mixture of the ceramic. XRD (X-Ray Diffraction) determination was done to determine the crystal structure. The component analysis was measured with XRF (X-Ray fluorescence). From the research result, white clay is nicely made by ceramic materials if mixed with sulfate calcium (CaSO4), limestone, iron sand, and chaff ash.